The European Larynx Organ Preservation Study [MK-3475-C44] - Wichmann, Gunnar; Wald, Theresa; Pirlich, Markus; Napp, Joanna; Münter, Ina; Asendorf, Thomas; Tostmann, Ralf; Vogt, Jeannette; Vogel, Kathrin; Meuret, Sylvia; Stoehr, Matthaeus; Zebralla, Veit; et al. (Frontiers in Oncology, 2024)
The European Larynx Organ Preservation Study (ELOS; NCT06137378) is a prospective, randomized, open-label, two-armed parallel group controlled, phase II multicenter larynx organ preservation (LOP) trial in locoregionally advanced (LA) stage III, IVA/B head and neck squamous cell carcinoma of the larynx or hypopharynx (LHSCC) amenable for total laryngectomy (TL) with PD-L1 expression within tumor tissue biopsy, calculated as CPS ≥ 1. Induction chemotherapy (IC) with docetaxel and cisplatin (TP) followed by radiation will be compared to TP plus PD-1 inhibition by pembrolizumab (MK-3475; 200 mg i.v. starting day 1 q3w for 17 cycles). After a short induction early response evaluation (ERE) 21 ± 3 days after the first cycle of IC (IC-1), responders achieving endoscopic estimated tumor surface shrinkage (ETSS) ≥30% will get an additional two cycles of IC followed by intensity-modulated radiotherapy 70–72 Gy (EQD2/α/β = 10) aiming at LOP. Nonresponders (ETSS < 30% or progressing disease) will receive TL and bilateral neck dissection followed by postoperative radiation or chemoradiation as recommended by the clinic’s multidisciplinary tumor board. Pembrolizumab treatment will be continued in the intervention arm regardless of ETSS status after IC-1 in both responders and laryngectomized nonresponders, independent of subsequent decisions on adjuvant therapy after TL. Clinical Trial Registration clinicaltrials.gov, identifier NCT06137378.